Specificities of secretion and uptake of exosomes and other extracellular vesicles for cell-to-cell communication - Mathieu, Mathilde; Martin-Jaular, Lorena; Lavieu, Grégory; Théry, Clotilde (Nature cell biology, 2019)
The ability of exosomes to transfer cargo from donor to acceptor cells, thereby triggering phenotypic changes in the latter, has generated substantial interest in the scientific community. However, the extent to which exosomes differ from other extracellular vesicles in terms of their biogenesis and functions remains ill-defined. Here, we discuss the current knowledge on the specificities of exosomes and other types of extracellular vesicles, and their roles as important agents of cell-to-cell communication. In this Perspective, Théry and co-authors discuss our current understanding of the biogenesis, secretion and uptake of exosomes and extracellular vesicles.